UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN SENI BUDAYA MENGENAI KONSEP, UNSUR, PRINSIP, BAHAN, DAN TEKNIK DALAM BERKARYA SENI RUPA MELALUI PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS VISUAL PADA SISWA KELAS XII MIPA-1 SMA NEGERI 1 SARIWANGI - Rudi Riswandi (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2022)
The results of the preliminary study, there were 50% of students of Class XII MIPA-1 SMA Negeri 1 Sariwangi their learning achievement in recognizing Concepts, Elements, Principles, Materials, and Techniques in Creating Fine Arts was still lacking, due to lack of knowledge of state defense efforts, and student motivation was still low. less, so that student learning outcomes in learning Arts and Culture is still low. The problem found in Class XII MIPA-1 SMA Negeri 1 Sariwangi is the lack of students understanding the learning of Cultural Arts about Concepts, Elements, Principles, Materials, and Techniques in Creating Fine Arts. This is evidenced by student learning outcomes in the previous school year with an average value of 65, meaning that the level of student understanding of Concepts, Elements, Principles, Materials, and Techniques in Creating Fine Arts is 65% with low criteria less than the predetermined KKM. ie 80. This is because learning techniques are still inadequate so that student learning outcomes are not good.The purpose of this study was to improve student learning outcomes through the use of visual-based learning media in the subject of Cultural Arts on Concepts, Elements, Principles, Materials, and Techniques in Creating Fine Arts in Class XII MIPA-1 SMA Negeri 1 Sariwangi.The method that will be used in this research is Kemmis and Mc.Taggart's Classroom Action Research (CAR). Classroom Action Research (CAR) has enormous potential to improve learning if it is implemented properly and correctly. Based on the results of research and discussion, they are as follows: The Learning Implementation Plan (RPP) cycle I has not been optimal because it has only reached 69.78%, while the Learning Implementation Plan (RPP) cycle II has reached 79.17%. This shows that there is an increase in teacher performance in preparing Learning Implementation Plans that have an effect on increasing student learning outcomes. The process of implementing learning by using visual-based learning media in improving student learning outcomes in the Cultural Arts subject on Concepts, Elements, Principles, Materials, and Techniques in Creating Fine Arts in Class XII MIPA-1 SMA Negeri 1 Sariwangi, that teacher activities in learning the first cycle was not optimal because it only reached 69.53%, while in the second cycle it reached 74.22%. This shows that the activity of teachers in the implementation of learning has increased. The results of the application of visual-based media on Concepts, Elements, Principles, Materials, and Techniques in Creating Fine Arts have increased including (1) the ability of students in cycle I, namely 70 cycles II, namely 82